Implementasi Websocket pada Pembacaan Ketinggian Air Lahan Gambut Sebagai Pencegahan Dini Kebakaran Berbasis LoRaWAN - Ristian, Uray; Hasfani, Hirzen; Kasliono, Kasliono; Halawa, Yasman; Kesuma Wijaya, Uray Syaziman (Journal of Information System Research (JOSH), 2024)
The monitoring system for water level in peatland is crucial for detecting the potential for fires, especially during the dry season. This study develops a water level monitoring system using a water float level sensor capable of detecting changes in water level in real-time. Data from the sensor is transmitted via the LoRa SX1278 Ra-02 module, enabling long-range data transmission. The system was tested under two conditions: Line of Sight (LoS) and Non-Line of Sight (NLoS), to measure the signal strength indicated by the Received Signal Strength Indicator (RSSI). In the LoS condition, the best RSSI value was recorded at -63 dBm at a distance of 15.5 meters, while in the NLoS condition, the lowest RSSI value reached -110 dBm at a distance of 148 meters. The results show that this system is effective in monitoring water levels in peatland with reliable data transmission, even in remote areas. The integration of the water float level sensor and LoRa technology in this system has the potential to be a valuable tool for preventing peatland fires through real-time monitoring of water conditions.